Sequential injection system with multi-parameter analysis capability for water quality measurement - Natcha Kaewwonglom (2018)
© 2015 Elsevier B.V. Abstract A simple sequential injection (SI) system with capability to determine multi-parameter has been developed for the determination of iron, manganese, phosphate and ammonium. A simple and compact colorimeter was fabricated in the laboratory to be employed as a detector. The system was optimized for suitable conditions for determining each parameter by changing software program and without reconfiguration of the hardware. Under the optimum conditions, the methods showed linear ranges of 0.2-10 mg L-1 for iron and manganese determinations, and 0.3-5.0 mg L-1 for phosphate and ammonium determinations, with correlation coefficients of 0.9998, 0.9973, 0.9987 and 0.9983, respectively. The system provided detection limits of 0.01, 0.14, 0.004 and 0.02 mg L-1 for iron, manganese, phosphate and ammonium, respectively. The proposed system has good precision, low chemical consumption and high throughput. It was applied for monitoring water quality of Ping river in Chiang Mai, Thailand. Recoveries of the analysis were obtained in the range of 82-119%.